Analyzing the adverse effects of childhood stress on adult anxiety behaviors by testing on male rats and addressing it with a period of aerobic exercise during adolescence - Bayat, Zahra; Guyo, Issack Shama; Esfanjani, Mitra; Esfanjani, Mina (Technium BioChemMed, 2022)
Anxiety is one of the most common diagnoses in psychiatry, which is twice as common in women as in men. Anxiety and depression disorders are significant because they affect a person's social and individual functioning and lead to severe economic and social damage, so they are expected to be debilitating diseases worldwide in the coming years. Considering the importance of treating stress disorders such as anxiety, which improves patients' social and personal functioning, and taking into account the side effects of drugs, researchers proposed sports activities as a non-pharmacological and effective occupational therapy method. But it is not clear whether the effects of exercise can be related to the regulation of the serotonergic system in the brain (especially anxiety behavior). Therefore, this research was designed and carried out to answer the following question: Will doing optional exercise (Running Wheel) and not mandatory exercise (Treadmill exercise) during adolescence be able to improve the ill effects of MS? In this research, six pregnant mice were used. After giving birth, their babies experienced the stress of separation from their mother for 12 days between the 2nd and 14th days after birth, and then from the 28th day, they exercised with the Running Wheel for a month. The number of rats was 8 for behavioral tests and 4 for molecular tests. In the model implemented in this research, after birth, mouse babies are separated from their mother for 180 minutes every day for 12 days (from the second day of birth to the 14th day after birth) and placed in a separate cage. This protocol is so-called. It is called Maternal Neonatal Separation or childhood stress. The results of this research determined that childhood stress in the form of separation from the mother is capable of causing anxiety behaviors in adult male rats. On the other hand, the results of this research determined that optional exercise with running wheels during adolescence can reduce the adverse effects of stress and anxiety-related behaviors.